2007
DOI: 10.1249/mss.0b013e3181238a2b
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Static Stretching Improves Exercise Performance

Abstract: This study suggests that chronic static stretching exercises by themselves can improve specific exercise performances. It is possible that persons who are unable to participate in traditional strength training activities may be able to experience gains through stretching, which would allow them to transition into a more traditional exercise regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
89
0
20

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(116 citation statements)
references
References 29 publications
5
89
0
20
Order By: Relevance
“…The primary aim of stretching is to maintain or improve flexibility. It has also been suggested that stretching may prevent injury (1), reduce delayed onset muscle soreness (9), and performed chronically can enhance performance (10), though these claims are more controversial not least because the processes by which these effects may arise are complex. Nevertheless, it is widely accepted that flexibility is an important component of general fitness, and it is likely that there is a certain minimum range of motion required to safely and optimally perform a given activity.…”
Section: Introductionmentioning
confidence: 99%
“…The primary aim of stretching is to maintain or improve flexibility. It has also been suggested that stretching may prevent injury (1), reduce delayed onset muscle soreness (9), and performed chronically can enhance performance (10), though these claims are more controversial not least because the processes by which these effects may arise are complex. Nevertheless, it is widely accepted that flexibility is an important component of general fitness, and it is likely that there is a certain minimum range of motion required to safely and optimally perform a given activity.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the widespread acceptance and use of stretching exercises as a component of exercise training, there is limited research documenting the benefits derived from regular stretching training program. Hunter and Kokkonen reported that flexibility training increases vertical jump and/or sprint performance [11,12]. Dintiman found that 8 weeks of static stretching and sprint training increase flexibility and running speed significantly [21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are only a few studies in the literature investigating chronic effects of stretching training on athletic performance and they report elevations in strength performance [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In general, PNF contract-relax techniques are the best for increasing ROM, along with static stretching. In static stretching, holding each stretch is recommended for 15 [35] or 30 [36][37][38] s. The number of repetitions varies, with some studies reporting three [36] or four repetitions [38] showing benefits. Sustained increases in ROM have been demonstrated when programmes are performed daily or at least 2-3 times per week [7].…”
Section: Flexibility -Angela Forsyth Pt Dpt -United States Of Americamentioning
confidence: 99%